THE MEANING OF NASEEM'S LOVE REFLECTED IN VIC SARIN'S PARTITION MOVIE (2007): A HUMANISTIC PSYCHOLOGICAL APPROACH - ARIYANTO, NIKA (2011)
This study is proposed to reveal how the meaning of Naseem's love reflected in Partition directed by Vic Sarin which is published in 2007. The object of the study is the Partition movie directed by Vic Sarin. The objectives of the study are to analyze the structural elements in the movie and to analyze the meaning of love based on a humanistic psychological approach. The writer employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie and script of Partition and the secondary data source is information related to the primary data source, website, and book on humanistic approach. The method of collecting data is observation and library review. The method of analyzing data is descriptive technique. Based on the analysis, the researcher draws two conclusions: first, based on the structural analysis, Vic Sarin wants to deliver a message that love can defeat anything and it is the master key to open the gates of happiness. Second, based on the humanistic psychological analysis, Vic Sarin wants to reflect that the meaning of love is being represented by Naseem's love and belongingness needs.